Spectral-converting study of La1-m-nErmYbnOCl (m=0.001-0.2, n=0-0.1) phosphors - Park, Sangmoon; Cho, So-Hye (ELSEVIER SCIENCE BV, 2014)
Optical materials composed of La1-m-nErmYbnOCl (m=0.001-0.2, n=0-0.1) solid solution were prepared via a solid-state reaction using excess NH4Cl flux at 950 degrees C for 30 min. X-ray diffraction patterns of La1-mErnOCl were compared upon altering the molar ratios of the flux to the La3+ (Er3+, Yb3+) ions. By means of photoluminescence spectra, the dependence of the luminescence intensity as a function of the Er3+ content and the color CIE coordinates of the Er3+-doped layered LaOCl compounds were also investigated under excitation by near-ultraviolet (NUV) and visible light. The spectral conversion properties of Er3+ and Er3+-Yb3+ ions doped into LaOCl phosphors were elucidated under diode-laser irradiation of 980 nm in wavelength. The desired up-conversion of the emitting light, passing throughout the green, orange, and red regions of the spectrum, was achieved by appropriate Er3+ and/or Yb3+ concentrations in the LaOCl host structure under 980-nm-excitation light, while its mechanism in the phosphors was described by an energy-level schematic. Up-conversion emission spectra and the dependence of the emission intensity on pump power in the La0.89Er0.1Yb0.01OCl phosphor were investigated under diode-laser irradiation of both wavelengths, 980 and 1550 nm. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: UP-CONVERSION LUMINESCENCE; ER3+; GREEN; CRYSTAL; LAOCL; LASER; IONS